The monthly rhythms of aviation: a global analysis of passenger air service seasonality - Dobruszkes, Frédéric; Decroly, Jean-Michel; Suau-Sanchez, Pere (Elsevier, 2022)
Aviation seasonality has been acknowledged for a long time, but no global picture is available. Our paper fills this gap by conducting a worldwide analysis of monthly passenger air services at the airport level, and discussing factors that shape this temporality. Our study found that 36% of airports worldwide (accounting for less than 12% of seats) experience a significant degree of seasonality, and that larger airports are less affected. On the one hand, diverse travel purposes related to larger cities, hubbing, physical geography, remoteness and appropriate weather throughout the year induce stable seat capacity. On the other hand, climate profiles and institutional factors are key factors of peaks. Aviation seasonality has impacts for airport funders and managers, regional development and scholars.
Keywords: Aviation seasonality; Air services; Temporal patterns; Spatial patterns of seasonality